Regrowth of serotonin axons in the adult mouse brain following injury - Jin,Y; Dougherty,SE; Wood,K; Sun,L; Cudmore,RH; Abdalla,A; Kannan,G; Pletnikov,M; Hashemi,P; Linden,DJ (Neuron, 2016)
It is widely believed that damaged axons in the adult mammalian brain have little capacity to regrow, thereby impeding functional recovery after injury. Studies using fixed tissue have suggested that serotonin neurons might be a notable exception, but remain inconclusive. We have employed in vivo two-photon microscopy to produce time-lapse images of serotonin axons in the neocortex of the adult mouse. Serotonin axons undergo massive retrograde degeneration following amphetamine treatment and subsequent slow recovery of axonal density, which is dominated by new growth with little contribution from local sprouting. A stab injury that transects serotonin axons running in the neocortex is followed by local regression of cut serotonin axons and followed by regrowth from cut ends into and across the stab rift zone. Regrowing serotonin axons do not follow the pathways left by degenerated axons. The regrown axons release serotonin and their regrowth is correlated with recovery in behavioral tests.